Development of innovative import substitution in the agro-industrial complex as a key factor in overcoming interregional differentiation and depression of agrarian-oriented and highly subsidized North Caucasian republics - TSKHURBAEVA, FATIMAT KHASBIEVNA; DAVLETBAEVA, NAZGUL’ BAKYTOVNA; DZOBELOVA, VALENTINA BATRAZOVNA; POLONKOEVA, FERDAUS YAKHIEVNA; IMANBEKOVA, AINAGUL MAKSUTOVNA (The journal of contemporary issues in business and government, 2020)
The growth of globalization processes, the aggravation of competition and the protracted economic and technological sanctions against the Russian Federation have necessitated adjusting the strategic goals that are being addressed within the context of import substitution. The Russian policy of import substitution in the agricultural sector should be implemented on the basis of large-scale technological modernization of agro-industrial production, the systematic use of innovations at all stages of the production cycle and the creation of conditions for diversification of production. The practice of implementing the strategy of import substitution in the Russian agrarian economy over the past five years has already made it possible to form a stable trend of growth in production of certain types of agricultural products. At the same time, the competitiveness of Russian agricultural products is still quite low due to the low productivity of agricultural machinery, backwardness of selection and genetic engineering, the lack of domestic seeds, etc. No less relevant limiting factor is the lack of an integral concept of innovative import substitution, the imperfection of tools for neutralizing and squeezing out imports by business entities. In these conditions, in our opinion, it is necessary to direct the entire natural resource and scientific and technical potential of the national economy to import substitution, because under current conditions there is no other way to ensure the economic and food security of the Russian Federation. The study of the morphogenesis of the process under consideration made it possible to establish that the features of building and implementation of the import substitution policy in the conditions of an innovation-oriented economy have not yet been analysed; the specific advantages and weak links of import substitution strategies have not been identified. There is still no single interpretation of the main categories; the possibilities and limitations of implementation of import substitution policy in the context of the need to increase the level of innovative activity have not been substantiated. All this, of course, requires the immediate development of theoretical and methodological approaches to the content of the strategy and tools for import substitution, taking into account the peculiarities of the Russian agrarian economy, all this determined the choice of our research topic.